Edge disturbance drives liana abundance increase and alteration of liana–host tree interactions in tropical forest fragments. Issue 8 (2nd April 2018) - Campbell, Mason J.; Edwards, Will; Magrach, Ainhoa; Alamgir, Mohammed; Porolak, Gabriel; Mohandass, D.; Laurance, William F.
Abstract: Closed‐canopy forests are being rapidly fragmented across much of the tropical world. Determining the impacts of fragmentation on ecological processes enables better forest management and improves species‐conservation outcomes. Lianas are an integral part of tropical forests but can have detrimental and potentially complex interactions with their host trees. These effects can include reduced tree growth and fecundity, elevated tree mortality, alterations in tree‐species composition, degradation of forest succession, and a substantial decline in forest carbon storage. We examined the individual impacts of fragmentation and edge effects (0–100‐m transect from edge to forest interior) on the liana community and liana–host tree interactions in rainforests of the Atherton Tableland in north Queensland, Australia. We compared the liana and tree community, the traits of liana‐infested trees, and determinants of the rates of tree infestation within five forest fragments (23–58 ha in area) and five nearby intact‐forest sites. Fragmented forests experienced considerable disturbance‐induced degradation at their edges, resulting in a significant increase in liana abundance. This effect penetrated to significantly greater depths in forest fragments than in intact forests. The composition of the liana community in terms of climbing guilds was significantly different between fragmented and intact forests, likely because forest edges had more small‐sized trees favoring particular liana guilds which preferentially use these for climbing trellises. Sites that had higher liana abundances also exhibited higher infestation rates of trees, as did sites with the largest lianas. However, large lianas were associated with low‐disturbance forest sites. Our study shows that edge disturbance of forest fragments significantly altered the abundance and community composition of lianas and their ecological relationships with trees, with liana impacts on trees being elevated in fragments relative to intact forests. Consequently, effective control of lianas in forest fragments requires management practices which directly focus on minimizing forest edge disturbance. Abstract : Lianas proliferate in tropical forest fragments and compete with trees for resources. Edge disturbance is the primary driver of liana proliferation in fragments. Liana abundance and size (dbh) determine the probability of tree infestation by lianas.